Web programming with Dart - Belchin, Moises; Juberias, Patricia (Expert's voice in Web development., 2015)
Web Programming with Dart is for programmers who want to master the new Dart programming language from Google, and also web developers who want to understand how Dart can integrate perfectly with HTML5 and CSS3. With this book you will understand the ins and outs of the language, how the tools work, and how to get the most from the core functions and libraries. Web Programming with Dart is a practical, example-led book, with case studies involving developing UI animations for the web, working with web services such as JSON, server side Dart applications, and the new Polymer.dart library for advanced HTML UI web components generation. Take a full tour of Dart's core features and its advanced functionality Learn the tools that come with Dart SDK and the most important libraries. Additionally you will work with the newest Polymer.dart library for web component creation. Develop your own command-line and server side applications and, of course, web applications with Dart.